Evaluation of Wheat Grain and Processing Quality Under Fusarium Head Blight Control Using Strong Oxidizing Radicals - Huanhuan Zhang; Bo Zhang; Huagang He; Lulu Zhang; Xinkang Hu; Chundu Wu (Foods)
Wheat plays a crucial role in global food security; however, in recent years, Fusarium Head Blight (FHB) has severely impacted both wheat yield and quality. Strong oxidative free radicals, with high oxidation potential and rapid reaction rates, offer an effective approach for pollutant degradation and microbial inactivation. In this study, the control effect of strong oxidizing radicals on FHB was evaluated by comparing the untreated control group (JM23), which was infected with FHB, to the experimental group (FG06), which was treated with strong oxidizing radicals following FHB infection. The results show that FG06 achieved a control effectiveness of 87.87%. The study also assessed grain characteristics and milling quality. Statistical analysis revealed that FG06 had a slightly lower flour extraction rate (71.24%) compared to the control wheat (JM23), but it exhibited competitive flour whiteness (81.30) and a gluten index of 85.50%. The dough stability at 10 min was 27.00 FE, while several gelatinization parameters were significantly lower than JM23. However, FG06 had higher protein content (10.94%), flour protein content (10.70%), ash content (0.58%), wet gluten content (28.70%), dry gluten content (9.40%), and sedimentation value (73.00 mL), all significantly higher than those of JM23. Additionally, FG06 had a gelatinization temperature of 68.61 °C, similar to JM23. Overall, Strong oxidizing radicals as an alternative to conventional pesticides not only effectively controls FHB but also maintains or even enhances wheat milling and processing quality, promoting more sustainable agricultural practices.